Rate of bacteria-induced strength deterioration of banana fiber as a potential alternative geotextile material for temporary access road - Silang, Jayson L.; Villaraza, Michael R.; Torio-Kaimo, Lestelle V. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The Philippines is located in a region where typhoons and landslides frequently occur. When primary roads are blocked, temporary access roads playa very important role in delivering relief and rescue operations to affected areas. The local banana industry produces a huge amount of organic wastes each year. In order to find new uses for these unwanted banana parts, the tensile strength properties of banana fiber are investigated to determine its suitability as an alternative natural geotextile material. This study focuses on the rate of biological deterioration in the strength of banana fiber with the use of Effective Microorganisms (EM-I) bacteria. Based on the test results, the tensile strength of banana fiber did not meet the minimum requirement set by AASHTO M-288 making it an unsuitable alternative material as natural geotextile for temporary access roads. In terms of strength deterioration, the double ply banana fiber deteriorates at a rate of 2.629% (relative to its initial strength) per day when the moisture content is around 29.08%. The rate of deterioration in tensile strength of single ply fiber is found to be higher than that of double ply fiber by 2.45%. Due to the inconsistency in the sample characteristics, there is no significant trend derived from the stress-strain relationship.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Geotextiles; Bananas; Dirt roads